PF.12 Longitudinal Data on Fetal Thigh Soft-Tissue Parameters and Its Role in the Prediction of Birthweight. (26th April 2013) - O'Connor, CI; Farah, N; O'Higgins, A; Grant, T; Fitzpatrick, C; Stuart, B; Turner, MJ; Kennelly, MM
Abstract : Objective: To profile longitudinal changes in the fetal mid thigh muscle and subcutaneous tissue measurements in fetuses with a normal growth velocity in euglycemic pregnancies and evaluate the association between mid thigh parameters and birthweight. Methods: A prospective longitudinal study of 351 singleton fetuses in euglycemic pregnancies. Reliability of fetal abdominal subcutaneous tissue (FAST) measurements and mid thigh indices including thigh muscle (TM) and thigh fat (TF) between two operators was also reviewed. Results: The FAST and fetal mid thigh muscle and fat in AGA fetuses show a significant increase with gestational age. At 28 weeks gestation the Abdominal circumference, TF, FAST and EFW centile were all found to be statistically significant predictors of birthweight. Using backwards stepwise linear regression to find the optimal multivariate model for predicting birthweight a combination of EFW centile and TF were found to be the best predictors. At 37 weeks optimal multivariate model for BW prediction was EFW centile, FAST and TF. The results reveal acceptable reproducibility for fetal mid thigh muscle and fat for a single operator and between operators. Conclusion: This prospective study provides reference ranges for fetal mid thigh fat and muscle throughout gestation in fetuses with a normal growth velocity. The inclusion of fetal mid thigh fat in the birthweight algorithm improves the predictive power of birthweight estimation at 28 weeks and 37 weeks. This information is important to explore the role of fetal mid thigh in the detection of fetal IUGR at point estimations of EFW within normal centiles.